Distinct Patterns of Automatic and Controlled Incongruent Information Processing in the Human Brain - Du, Jialin; Zhu, Yu; Zhao, Chengtian; Yang, Dongju; Yu, Tao; Zhang, Xiaohua; Ren, Liankun; Wang, Yuping (Frontiers in Human Neuroscience, 2022)
It is a fundamental ability to discriminate incongruent information in daily activity. The underlying neural dynamics, however, is still unclear. Using stereo-electroencephalography (SEEG), we herein investigated the fine-grained and different states of incongruent information processing in patients with refractory epilepsy who underwent intracranial electrodes implantation. All patients performed delayed match-to-sample paradigm were designed in the sequential pairs of visual stimuli (S1 followed by S2). Participants were asked to discriminate whether the relevant feature of S2 was identical with S1 while ignoring the irrelevant feature. The spatiotemporal cortical responses that were evoked by different conditions were calculated and compared respectively in the context of brain intrinsic functional networks. In total, we obtained SEEG recordings from 241 contacts in gray matter. In the process of irrelevant incongruent information, the activated brain areas include superior parietal lobule, supramarginal gyrus, angular gyrus, inferior temporal gyrus and fusiform gyrus. By comparing the relevant incongruent condition with congruent condition, the activated brain areas include middle frontal gyrus, superior temporal gyrus, middle temporal gyrus, posterior superior temporal sulcus and posterior cingulate cortex. We demonstrated the dynamic of incongruent information processing with high spatiotemporal resolution and suggested the process of automatic detection of irrelevant incongruent information requires the involvement of local regions and a relatively few networks. Meanwhile, controlled discrimination of relevant incongruent information needs the participation of extensive regions and a wide range of nodes in the network. Furthermore, both frontoparietal control network and default mode network were engaged in the incongruent information processing.